Soluble Adenylyl Cyclase Controls Mitochondria-dependent Apoptosis in Coronary Endothelial Cells - Kumar, Sanjeev (American Society for Biochemistry and Molecular Biology, 2009)
The cAMP signaling pathway plays an essential role in modulating the apoptotic response to various stress stimuli. Until now, it was attributed exclusively to the activity of the G-protein-responsive transmembrane adenylyl cyclase. In addition to transmembrane AC, mammalian cells possess a second source of cAMP, the ubiquitously expressed soluble adenylyl cyclase (sAC). However, the role of this cyclase in apoptosis was unknown. A mitochondrial localization of this cyclase has recently been demonstrated, which led us to the hypothesis that sAC may play a role in apoptosis through modulation of mitochondria-dependent apoptosis. To prove this hypothesis, apoptosis was induced by simulated in vitro ischemia or by acidosis, which is an important component of ischemia. Suppression of sAC activity with the selective inhibitor KH7 or sAC knockdown by small interfering RNA transfection abolished endothelial apoptosis. Furthermore, pharmacological inhibition or knockdown of protein kinase A, an important cAMP target, demonstrated a significant anti-apoptotic effect. Analysis of the underlying mechanisms revealed (i) the translocation of sAC to mitochondria under acidic stress and (ii) activation of the mitochondrial pathway of apoptosis, i.e. cytochrome c release and caspase-9 cleavage. sAC inhibition or knockdown abolished the activation of the mitochondrial pathway of apoptosis. Analysis of mitochondrial co-localization of Bcl-2 family proteins demonstrated sAC- and protein kinase A-dependent translocation of Bax to mitochondria. Taken together, these results suggest the important role of sAC in modulating the mitochondria-dependent pathway of apoptosis in endothelial cells.